(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf YHOGdbGOQ Hf CMeO Hf ecJhe Hf CMeO Hf eMeO Hf oSdje GdbjSj s)
(3ChdgG (B:s
(3aUd ef heG aj GddaX eaQO aeQGYGI GddaX ajeG GJUd HgeG Ch HeG CTHggeG s
(3BNQgG (B:s
(3dbO XffJg dCf eaYhd HCf SO eSQ GdLedI GdeaSQI hgPG cdg HGWd Je GdeLdO GdKGfj aEf dRe GdJChjd dRe GdaJM s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B672(3g`s
(3fSNI ajgG VHW hgj Yf fSNI GdeDda hHChdgG Jedc SfI (B986(3g`s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GdfMhs